Análise de camadas e misturas de pigmentos em obras de artes utilizando a técnica Kα/Kβ por fluorescência de raios X - Castro, Lais Nogueira Corrêa e (2019)
In this work the X-Ray Fluorescence technique was used to assist two problematic aspects applied in the analysis of pigments in frames: the first one was about the location of the pigments in their respective pictorial layers in a painting. And the second one, was the question of the positioning of the equipment of X-ray fluorescence in materials analysis. The techniques of X-Ray Fluorescence and Optical Microscopy were used. Samples were prepared containing layers and mixtures of commercial pigments, of different historical periods, applied on canvas, using conventional painting techniques. The XRF technique was used to study the distribution of the pigments in the pictorial layers in each sample, from the ratios between the energy lines Kα and Kβ for the key elements that characterize these pigments by XRF. Throught these data it was possible to obtain the calibration curves of each key element of the analyzed pigments. Later it was applied the technique Kα / Kβ in the data referring to the artifacts of ancient Egypt from the Egyptian collection of the National Museum of UFRJ. The Optical Microscopy was used to verify the quality of the samples created and it was possible to visualize clearly the layers of pigments. An automatic positioning table was developed for the LIN XRF system. The analyzes were performed using the portable EDXRF system. This system consists of an X-ray Mini-X tube of Amptek and an X-123 SDD detector of Amptek operating at a voltage of 30 kV and a current of 40 μA. The resolution of the proposed questions will assist in future work in the area of archeometry, since it will allow the majority of the analyzes involving pigments to be carried out in a non-destructive and in situ way, with the most accurate results, without the need for sample collection.